Impact of Air Pollution on Residents' Medical Expenses: A Study Based on the Survey Data of 122 Cities in China - Liu, Huan; Hu, Tiantian; Wang, Meng (Frontiers in Public Health, 2021)
Background: With the development of the social economy, air pollution has resulted in increased social costs. Medical costs and health issues due to air pollution are important aspects of environmental governance in various countries. Methods: This study uses daily air pollution monitoring data from 122 cities in China to empirically investigate the impact of air pollution on residents' medical expenses using the Heckman two-stage and instrumental variable methods, matching data from the 2018 China Health and Retirement Longitudinal Study (CHARLS) survey. Results: The study found that poor air quality, measured by the air quality index (AQI), significantly increased the probability of chronic lung disease, heart disease, and self-rated poor health. Additionally, the AQI (with an effect of 4.51%) significantly impacted health-seeking behaviour and medical expenses. The medical expenditure effects of mild, moderate, severe, and serious pollution days were 3.27%, 7.21%, 8.62%, and 42.66% , respectively. Conclusion: In the long run, residents’ health in areas with a higher air pollution index, indicating poor air quality, is negatively impacted. The more extreme the pollution, the higher the probability of residents' medical treatment and the subsequent increase in medical expenses. Group and regional heterogeneity also play a role in the impact of air pollution on medical expenses. Compared with the existing literature, this study is based on individuals aged 15 years and above and produces reliable research conclusions.